Arthroscopy pull through for management of eminentia tibia fracture in 15 years old adolescent: a case report - Maha Putra, Anak Agung Gde Duta; Maharjana, Made Agus (International Journal of Research in Medical Sciences, 2020)
Tibial eminence fractures are rare injuries. Multiple treatment techniques are described and there is a lack of consensus with regard to the choice of treatment. In this case, we present the left eminentia tibia fracture which stabilized using arthroscopy pull through technique in a 15 years old male adolescent. A male 15 years old adolescent complained of pain on his left knee after climbing a tree and jumped with his left knee in hyperextention. On physical examination, tenderness was felt around the apex of patella. Left knee X-Ray confirmed a fracture of eminentia tibia. On arthroscopic evaluation, there was a fracture of medial eminentia tibia meyers and mckeever IIIA. The fractures were treated by using 1 mm ethibond which was inserted through the anterior cruciate ligament and pull through the tibia plateau. 10 weeks evaluation after the procedure, patient was able to walk independently with full weight bearing and was able to flex his knee in 130˚ and full extension without any pain. Management of displaced fracture of eminentia tibia is somewhat controversial and the ideal method of ﬁxation has not been deﬁned. In this patient, there were perfect anatomic and functional outcome without any serious complication. Arthroscopic reduction and internal fixation by pull through suture provide perfect anatomic and functional outcome for displaced type II and type III tibial eminence fracture.